2011
DOI: 10.17221/124/2008-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Separation and character analysis of anthocyanins from mulberry (Morus alba L.) pomace

Abstract: Zhang W., He J., Pan Q., Han F., Duan C. (2011): Separation and character analysis of anthocyanins from mulberry (Morus alba L.) pomace. Czech J. Food Sci., 29: 268-276.Mulberry pomace, as a by-product of juice and wine making, was investigated as a potential source of natural anthocyanins. The results showed that anthocyanin contents in mulberry pomace from two varieties were above 250 mg/100 g, that is 74%-79% of that in mulberry whole fruit. Thus, mulberry pomace could be a potential anthocyanins source. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…As charted in Fig. 1(b), (c), we found that C3G (47.91%) and C3R (52.09%) were the main anthocyanin fractions of AC, which agrees with related studies 22–24 . In detail, peak#1 has a m/z value of 449.1 [M + H] + and the m/z value of its fragment ions was 287.0, indicating that this peak was anthocyanin glucosides.…”
Section: Resultssupporting
confidence: 88%
“…As charted in Fig. 1(b), (c), we found that C3G (47.91%) and C3R (52.09%) were the main anthocyanin fractions of AC, which agrees with related studies 22–24 . In detail, peak#1 has a m/z value of 449.1 [M + H] + and the m/z value of its fragment ions was 287.0, indicating that this peak was anthocyanin glucosides.…”
Section: Resultssupporting
confidence: 88%
“…Many believe that one glass of this wine per day improves health by cleaning the organism from impurities and enables the ejection of fecal residues in the intestines. Besides, mulberry fruits are rich in anthocyanins, the primary source of antioxidant activities [28][29][30][31][32][33][34]. Active biomolecules of different mulberry species are kuwanon I, kuwanon I hexamethyl ether, kuwanon I octamethyl ether, 2'-hydroxy-2,4,4'-trimethoxychalcon and 2'-hydroxy-3'-prenyl-2,4,4'-trimethoxychalcone III, mulberrofuran T and kuwanon E, morusin, mulberrofuran D, G, K, kuwanon H, mulberroside A, cis-mulberroside A, oxyresveratrol, isoquercetin, moracin E, F, G and kuwanon D, E, F, deoxynojirimycin-1 etc.…”
Section: Mulberry As a Medicinementioning
confidence: 99%
“…These molecules possess healing properties like adstringent, anti-HIV, anti-inflammatory, the purgative effect etc. [30][31][32][33]. Rubraflavones A, B, C, D, which act as laxatives, purgatives, against urinary infections and weakness, were isolated from the root of red mulberry.…”
Section: Mulberry As a Medicinementioning
confidence: 99%
“…Besides, fruits are also a potent source of anthocyanins, which play a key role in antioxidant activity. This also offers the possibility of industrial use of mulberry as a source of anthocyanins as a natural food colorant, which could enhance the overall profitability of sericulture and holds promise for tropical sericulture countries for profiting from industrial anthocyanin production from mulberry through better anthocyanin recovery [39][40][41][42][43][44][45].…”
Section: Medicinal Properties Of Mulberrymentioning
confidence: 99%